Proteins that appear to be associated with pili in Neisseria gonorrhoeae. - Muir, L L (1988)
Pili of Neisseria gonorrhoeae are thought to be composed entirely of identical subunits, called pilin, that self-assemble in vitro. Previous pilus purification methods have relied on this latter point, and dissociation and reassociation of pilin subunits has yielded pilin preparations of high purity. Such a procedure could result in the loss of any pilus-associated proteins. We have developed a procedure for the isolation of intact native pili in a deoxycholate-urea buffer in which the pili are fractionated on the basis of size and hydrophobicity. Electron microscopy indicates that the pili are largely free from outer membrane vesicles and other cellular material. Electrophoretic analysis has shown that a number of proteins copurify with pilin. Antibodies to these proteins could be removed from an antiserum against whole piliated cells by absorption with piliated cells but not by absorption with nonpiliated cells. Hence, our results indicate that these proteins could be pilus associated.